Nicotine Hypersensitivity in Inflammatory Dermatoses: A Systematic Review of Evidence for Nicotine as a Cutaneous Hapten - Sudan, Bernard J.L. (HM Publisher, 2025)
Background: Inflammatory dermatoses, such as seborrheic dermatitis (SD) and atopic dermatitis (AD), affect a significant portion of the population, yet their precise etiology often remains debated. Nicotine, a ubiquitous alkaloid primarily associated with tobacco but also present in certain plants and therapeutic products, has been proposed as a potential hapten capable of triggering hypersensitivity reactions manifesting as inflammatory skin conditions. This systematic review aimed to evaluate the existing evidence supporting the role of nicotine as a cutaneous hapten involved in the pathophysiology of inflammatory dermatoses. Methods: A systematic literature search was conducted using PubMed, Embase, and Google Scholar databases for studies published between January 2014 and December 2024. Keywords included